Legal Arrangements and Remedies for Abandoned Land: A Normative Study - Diana, Diana; Aswari, Aan (Manunggal Halim Jaya, 2023)
This study aims to find out the legal arrangements regarding abandoned land regarding land ownership rights and find out the legal remedies that can be taken by holders of ownership rights over abandoned land. This study uses the Normative legal research method, namely approaching legal norms or substance, legal principles, legal theory, legal arguments and comparative law. The results of this study indicate that overcoming the abandoned land phenomenon is a big task for the government. Based on this reason, Government Regulation No. 20 of 2021 concerning Controlling Abandoned Areas and Lands and participating in implementing Law Number 5 of 1960 concerning Basic Agrarian Basic Regulations. The erasure of land rights due to neglect. Through the inventory stage which is carried out no later than 2 (two) years from the issuance of land rights, management rights, or basis of land tenure. The results of this implementation are then processed into land data indicated as abandoned, divided into 3 stages, Abandoned Land Evaluation, Abandoned Land Warning and Abandoned Land Determination. Legal remedies taken by landowners who have been neglected through ordinary legal remedies and extraordinary legal remedies. Besides that, through non-litigation channels, namely, arbitration, negotiation, mediation, conciliation, expert reasoning. The author's recommendation is the need to carry out supervision and counseling regarding procedures regarding the importance of ownership of land rights. To the public, in this case the owner of land rights should have consideration in choosing legal remedies that are not always only through litigation or court. However, many things must be considered, such as the relatively long time, unmeasured costs, court decisions often cannot be executed immediately, and often court decisions are colored by the interference of other parties. Therefore, it is necessary to reconsider the settlement through non-litigation channels which is actually faster and cheaper than through litigation which has many obstacles.